Effects of benzalkonium chloride adaptation on controlling Listeria monocytogenes biofilms and its growth in food - Honghui Wang; Yamin Ren; Yanhong Tang; Mingyu Zhang; Xiaoli Zou (Czech Journal of Food Sciences)
In this study the eradication effectiveness of four commonly used disinfectants against benzalkonium chloride (BC) adapted and non-adapted biofilms of Listeria monocytogenes was compared and the effects of food preservatives on the growth of these strains were comparatively evaluated on pasteurised chicken sausage. After BC adaptation, the minimum inhibitory concentrations (MICs) of BC against planktonic bacteria of L. monocytogenes increased, while the MICs of chlorine dioxide remained unchanged. BC adapted strains showed stronger biofilm formation than the wild-type parents. When used at 1 × MIC, the eradication rates of chlorine dioxide on biofilm biomass, cell viability and biofilm extracellular polymeric substance were higher than BC. When used at the recommended concentrations, chlorine dioxide exhibited the highest efficiency in BC adapted and non-adapted biofilm eradication. Among the four food preservatives, nisin showed the highest inhibition of both BC adapted and non-adapted strains grown on pasteurised chicken sausage. Our data suggest that proper use of BC is required to reduce the exposure of L. monocytogenes to sublethal concentrations of BC and the emergence of BC adapted strains.